ANALISIS KESULITAN SISWA KELAS VIII DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL - Laia, Faomazatulo (Afore : Jurnal Pendidikan Matematika, 2024)
This study examines the challenges faced by eighth-grade students at State Junior High School 1 Lahusa in solving systems of linear equations with two variables. This study aims to elucidate the challenges faced by students in solving systems of linear equations with two variables. This study is qualitative and employs a descriptive methodology. The participants in this study were 24 eighth-grade students from SMP Negeri 1 Lahusa. Data analysis process include data reduction, data presentation, and conclusion drawing. Interviews and tests are data collection procedures that are used. The research findings indicate that 25% of students struggle with idea generation, 50% have difficulty understanding the topic, and 25% find it challenging to do calculations. The challenges arise from students' lack of accurate understanding of problem-solving strategies and skills. Conclusively, 8th-grade students at SMP Negeri 1 Lahusa have the greatest challenge in understanding issues. This study suggests that teachers' instructional design should aim to provide a question-and-answer forum to address students' challenges.